Molecular markers for leaf rust resistance gene Lr42 in wheat - Liu, Zhengli; Bowden, Robert L.; Bai, Guihua (My University, 2013)
Wheat leaf rust, caused by Puccinia triticina Eriks., is an important wheat foliar disease worldwide. Growing cultivars incorporating genetic resistance is one of the most effective approaches for disease control. Leaf rust resistance gene Lr42 was identified from a wheat relative, Aegilops tauschii Coss, and has been transferred into hard winter wheat. A previous study identified two markers closely linked to the gene on the short arm of chromosome 1D (1DS) using a near isogenic population, but flanking markers for Lr42 were not found. In this study, a new mapping population was developed from a cross between ‘KS93U50’ (a Lr42 carrier) and a susceptible parent, ‘Morocco’. An F[subscript 2] population was analyzed with all simple sequence repeat (SSR) markers available from chromosome 1D and F[subscript 2] plants and F[subscript 3] families were evaluated for seedling resistance to isolate PNMR, a rust isolate avirulent to Lr42. The F[subscript 2] and F[subscript 3] rust data showed that Lr42 was recessive. Seven markers formed the linkage group on 1DS. The Lr42 region was flanked by two simple sequence repeat (SSR) markers; Xwmc432 and Xgdm33 at 17 cM apart. The results confirmed that Lr42 is positioned on the distal end of chromosome 1DS. The flanking markers for Lr42 should be useful for map-based cloning and marker-assisted pyramiding of Lr42 with other leaf rust resistance genes.
Citation: Liu, Zhengli, Robert L. Bowden, and Guihua Bai. “Molecular Markers for Leaf Rust Resistance Gene Lr42 in Wheat.” Crop Science 53, no. 4 (2013): 1566–70. https://doi.org/10.2135/cropsci2012.09.0532.
Keywords: Wheat leaf rust; Puccinia triticina Eriks.; Lr42; Leaf rust resistance genes